Cerebrospinal Fluid of Patients With Alzheimer’s Disease Contains Increased Percentages of Synaptophysin-Bearing Microvesicles - Utz, Janine; Berner, Judith; Muñoz, Luis Enrique; Oberstein, Timo Jan; Kornhuber, Johannes; Herrmann, Martin; Maler, Juan Manuel; Spitzer, Philipp (Frontiers in Aging Neuroscience, 2021)
Introduction: In Alzheimer’s disease, the severity of symptoms is linked to a loss of synaptic density and the spread of pathologically hyperphosphorylated tau. The established cerebrospinal fluid markers Aβ, tau and phospho-tau reflect the histopathological hallmarks of Alzheimer’s disease but do not indicate disease progression. Such markers are of special interest, especially for trials of disease modifying drugs. Microvesicles are produced by stressed cells and reflect part of the metabolism of their cells of origin. Therefore, we investigated microvesicles of neuronal origin in cerebrospinal fluid. Material and Methods: We used flow cytometry to analyze microvesicles carrying tau, phospho-tau-Thr181, phospho-tau-Ser202Thr205, synaptophysin and SNAP-25 in the cerebrospinal fluid of 19 patients with Alzheimer’s disease and 15 controls. Results: The percentages of synaptophysin-bearing microvesicles were significantly higher in the cerebrospinal fluid of patients with Alzheimer’s disease than in the CSF of noninflammatory neurological disease controls. Tau, phospho-tau-Thr181, phospho-tau-Ser202Thr205, and SNAP-25 did not differ between the groups. The percentages of synaptophysin-bearing vesicles distinguished patients with Alzheimer’s disease from the controls (AUC = 0.81). Conclusion: The loss of synapses in Alzheimer’s disease may be reflected by synaptophysin-bearing microvesicles in the cerebrospinal fluid. Future studies are needed to investigate the possibility of using these MVs as a marker to determine the activity of Alzheimer’s disease.